Access to an Effective Remedy in European Asylum Procedures - Marcelle Reneman (Amsterdam Law Forum, 2008)
In this contribution the author tries to identify the meaning and content of the Community principles of effectiveness and effective judicial protection with regard to the right of access to an effective remedy in the context of the Common European Asylum System. With this purpose the relevant case-law by the Court of Justice, the European Court on Human Rights, the Committee against Torture and the Human Rights Committee will be discussed. On the bases of this case-law some general conclusions will be drawn regarding the right of access to an effective remedy and the lawfulness of certain limitations of this right, such as time-limits or the immediate enforcement of expulsion measures.